LINGUISTIC AND CULTURAL FEATURES OF INTERPERSONAL RELATIONS IN URBAN DISCOURSE - Zakirova Khilola Abduraxmanovna (Web of Journals Publishing, 2024)
This article explores the linguistic and cultural features of interpersonal relations within urban discourse, focusing on how language use in urban settings reflects and shapes social dynamics, identities, and cultural norms. Urban environments, with their diversity, complexity, and dynamic nature, offer a unique setting for examining communication practices. By analysing the linguistic strategies employed in various urban contexts—such as casual conversations, professional interactions, and public discourse—the article highlights how urban communication is influenced by both local and global cultural trends. It also examines how these linguistic practices play a role in identity construction, power dynamics, and social inclusion or exclusion in cities.
Keywords: Urban settings, interpersonal relations, urban environment, professional interactions, public discourse, social inclusion or exclusion, identity construction.